Prostate tumor attenuation in the nu/nu murine model due to anti-sarcosine antibodies in folate-targeted liposomes - Heger, Zbynek; Polanska, Hana; Merlos Rodrigo, Miguel Angel; Guran, Roman; Kulich, Pavel; Kopel, Pavel; Masarik, Michal; Eckschlager, Tomas; Stiborova, Marie; Kizek, Rene; Adam, Vojtech (Scientific reports, 2016)
Herein, we describe the preparation of liposomes with folate-targeting properties for the encapsulation of anti-sarcosine antibodies (antisarAbs@LIP) and sarcosine (sar@LIP). The competitive inhibitory effects of exogenously added folic acid supported the role of folate targeting in liposome internalization. We examined the effects of repeated administration on mice PC-3 xenografts. Sar@LIP treatment significantly increased tumor volume and weight compared to controls treated with empty liposomes. Moreover, antisarAbs@LIP administration exhibited a mild antitumor effect. We also identified differences in gene expression patterns post-treatment. Furthermore, Sar@LIP treatment resulted in decreased amounts of tumor zinc ions and total metallothioneins. Examination of the spatial distribution across the tumor sections revealed a sarcosine-related decline of the MT1X isoform within the marginal regions but an elevation after antisarAbs@LIP administration. Our exploratory results demonstrate the importance of sarcosine as an oncometabolite in PCa. Moreover, we have shown that sarcosine can be a potential target for anticancer strategies in management of PCa.
Keywords: kyselina listová; modely nemocí na zvířatech; Metallothionein; Male; monoklonální protilátky; Cell Line, Tumor; Liposomes; metalothionein; fosfatidylethanolaminy; Xenograft Model Antitumor Assays; vztah mezi dávkou a účinkem léčiva; Prostatic Neoplasms; mužské pohlaví; Folic Acid; Models, Biological; Tumor Burden; liposomy; xenogenní modely - testy protinádorové aktivity; Animals; lidé; biologické modely; Humans; zvířata; nádory prostaty; Phosphatidylethanolamines; Sarcosine; Disease Models, Animal; myši; tumor burden; zinek; Antibodies, Monoclonal; nádorové buněčné linie; Mice; Dose-Response Relationship, Drug; Zinc; sarkosin